Translating knowledge for action against stroke – using 5-minute videos for stroke survivors and caregivers to improve post-stroke outcomes: study protocol for a randomized controlled trial (Movies4Stroke). Issue 1 (December 2016) - Kamal, Ayeesha; Khoja, Adeel; Usmani, Bushra; Muqeet, Abdul; Zaidi, Fabiha; Ahmed, Masood; Shakeel, Saadia; Soomro, Nabila; Gowani, Ambreen; Asad, Nargis; Ahmed, Asma; Sayani, Saleem; et al.
Abstract Background Two thirds of the global mortality of stroke is borne by low and middle income countries (LMICs). Pakistan is the world's sixth most populous country with a stroke-vulnerable population and is without a single dedicated chronic care center. In order to provide evidence for a viable solution responsive to this health care gap, and leveraging the existing >70 % mobile phone density, we thought it rational to test the effectiveness of a mobile phone-based video intervention of short 5-minute movies to educate and support stroke survivors and their primary caregivers. Methods Movies4Stroke will be a randomized control, outcome assessor blinded, parallel group, single center superiority trial. Participants with an acute stroke, medically stable, with mild to moderate disability and having a stable primary caregiver will be included. After obtaining informed consent the stroke survivor-caregiver dyad will be randomized. Intervention participants will have the movie program software installed in their phone, desktop, or Android device which will allow them to receive, view and repeat 5-minute videos on stroke-related topics at admission, discharge and first and third months after enrollment. The control arm will receive standard of care at an internationally accredited center with defined protocols. The primary outcome measure is medication adherence as ascertained by a locally validated Morisky Medication Adherence Scale and control of major risk factors such as blood pressure, blood sugar and blood cholesterol at 12 months post discharge. Secondary outcome measures are post-stroke complications and mortality, caregiver knowledge and change in functional outcomes after acute stroke at 1, 3, 6, 9 and 12 months. Movies4Stroke is designed to enroll 300 participant dyads after inflating 10 % to incorporate attrition and non-compliance and has been powered at 95 % to detect a 15 % difference between intervention and usual care arm. Analysis will be done by the intention-to-treat principle. Discussion Movies4Stroke is a randomized trial testing an application aimed at supporting caregivers and stroke survivors in a LMIC with no rehabilitation or chronic support systems. Trial registration NCT02202330 (28 January 2015)